ChemInform Abstract: New Cassane‐Type Diterpenoids from Caesalpinia bonduc. Issue 52 (29th December 2014) - Wu, Lin; Wang, Xiaobing; Shan, Siming; Luo, Jun; Kong, Lingyi
Abstract The six new cassane‐type diterpenoids (I)‐(V) are isolated from the seed kernels of Caesalpinia bonduc.